Implications of the Talking Stick Method in Enhancing Students’ Arabic Speaking Skills in Islamic High School - Intan Kartika Dewi; Ahmad Fatoni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to evaluate the impact of the talking stick method on speaking and the teaching strategies of teachers on improving students' speaking abilities at MA Muhammadiyah 1 Plus in Malang City. This research uses a quantitative approach. The data is collected through observation and tests. The research population was class XI students, with a total sample of 30 students. This type of research is pre-experimental with a one-group pretest and post-test design method. The T-test results show a sig (2-tailed) value of 0.001 is obtained, which is smaller than 0.05 (0.001<0.05), which means that Ha is accepted. Meaning that there is an increase after treatment. So, the talking stick method has been proven to increase the Arabic vocabulary. Analysis results show that the Talking Stick method has been proven capable of increasing student participation in learning, as well as providing motivation and captivating interest in learning Arabic. Student activities during the learning process were also observed to have increased positively, starting from the pre-test to the post-test. This indicates that the Talking Stick method creates an interactive learning environment that supports student learning progress.